Evaluation of The Poedji Rochjati Score Card (PRSC) on Digital Platform @hamilku.id Based on The Delphi Method - Fadli, Sonny; Wibawa, Adhi Dharma; Eljatin, Dwinka Syafira (Institut Teknologi dan Bisnis STIKOM Bali, 2024)
The number of cases and deaths of mothers and babies in Indonesia is increasing, which is mediated by low-risk detection in early pregnancy, and a lack of knowledge resulting in the dissemination of pregnancy-related information tends to be poorly understood. As a solution to this problem, the purpose of this study was to analyze the effectiveness and usability of the Poedji Rochjati Score Card (PRSC) feature on the @hamilku.id Digital Platform based on the Delphi method. Qualitative research methods with technical observations were carried out online by obstetricians and gynecologists. The main focus of this research was usability testing involving 46 pregnant women who used the application and 9 randomly selected respondents. The assessment and evaluation were guided by the Delphi method, which involved two rounds of testing by six obstetricians and gynecologists. The results were descriptively analyzed. The findings showed that pregnant female respondents aged between 17 and 34 years had a higher education level, were dominated by people without jobs/housewives, were domiciled in Sidoarjo, had undergone antenatal care (ANC) ≤ 6 times, and had undergone ≥ 5 pregnancies. According to the PRS, 52.2% of pregnant women were classified as having high-risk pregnancies (HRPs). Based on the evaluation of the application from the usability aspect, 83.3% of the participants stated that the information was comprehensive and that the medical terminology was easy to understand. However, only half of them considered visualization in the form of images or animations to be very helpful in illustrating pregnancy risks. Delphi testing with obstetricians and gynecologists revealed that the digital PRSC features generated positive ratings, indicating that the tool is accurate, informative, easy to understand, and effective at improving the quality of health services. The second round showed an improvement in the quality and relevance of the digital PRSC features, with more diverse feedback from the respondents providing a broader perspective for future research and feature development. As a result, the digital PRSC feature can help individuals precisely and accurately identify pregnancy risks.